Who is the sky? [compact disc] - Byrne, David, 1952- (Matador Records, 2025)
In 2023, David Byrne began crafting new music after American Utopia, reflecting on life's meaning. The result is this album, a personal, cinematic, and joyful album created with Kid Harpoon and Ghost Train Orchestra, featuring Hayley Williams, St. Vincent, and Tom Skinner. It explores love, enlightenment, and human connection, blending avant-garde and pop, continuing Byrne's quest for unity in a chaotic world.